A disastrous history of the world chronicles of war, earthquake, plague and flood - Withington, John 1947- (Piatkus, 2010)
Tsunamis, earthquakes, floods, bird flu, international terrorism - the world seems to get more dangerous by the day. Or does it? John Withington's disturbing yet fascinating new book describes the worst things that have happened on Earth from the dawn of man to the present day. Part One chronicles all the major natural calamities - floods and earthquakes, volcanic eruptions, hurricanes and typhoons, plague and famine. Part Two describes in compelling detail the greatest man-made disasters - war and invasion, air raids, massacres, riots and terrorism, fires and explosions, shipwrecks, and air and train crashes. John Withington takes the reader on an epic journey through the annals of the nastiest things to have afflicted mankind. Out of all this horror, he has somehow fashioned a compulsively readble and entertaining book.